Intraocular pressure and visual field loss in primary angle closure and primary open angle glaucomas. Issue 6 (1st June 2003) - Gazzard, G; Foster, P J; Devereux, J G; Oen, F; Chew, P; Khaw, P T; Seah, S
Abstract : Aim: To compare the correlation between visual field loss and the pretreatment intraocular pressure (IOP) in primary angle closure glaucoma (PACG) and primary open angle glaucoma (POAG). Methods: In a cross sectional observational study of 74 patients (43 PACG, 31 POAG), pretreatment IOP was measured at presentation, before treatment was initiated. The severity of visual field loss was assessed by AGIS score, mean deviation (MD), pattern standard deviation (PSD), and corrected pattern standard deviation (CPSD). Glaucomatous optic neuropathy was assessed from simultaneous stereo disc photographs. Results: There was a stronger correlation between pretreatment IOP and the extent of visual field loss in PACG subjects than in those with POAG for both MD (PACG: Pearson correlation coefficient ( r ) = 0.43, p = 0.002; r 2 = 0.19), (POAG: r = 0.21, p = 0.13; r 2 = 0.04) and AGIS score (PACG: r = 0.41, p = 0.003; r 2 = 0.17), (POAG: r = 0.23, p = 0.19; r 2 = 0.05 respectively). No such associations were seen for pattern standard deviation (PSD) or corrected pattern standard deviation (CPSD) in either group (p> 0.29). Both horizontal and vertical cup-disc ratio were well correlated with severity of field loss but not with presenting IOP for either diagnosis. Conclusions: This is consistent with the hypothesis of a greater IOP dependence for optic nerve damage in PACG than POAG and, conversely, a greater importance of other, less pressure dependent mechanisms in POAG compared to PACG.